Kultberget på Stora Holm - Lönn, Marianne (In Situ Archaeologica, 2015)
Tuve 46 was a complex monument, a hillock which people have taken the trouble to cover with stones. Among the stones were graves, mounds of burnt stones, a special mound of stones at the highest point, a cult building and on one side of the hillock were post-holes, hearths, cooking-pits and the like. On the hillock were also several concentrations of flint flakes and a few broken or unfinished flint tools. The site has mainly been used during two periods of time, one is the late Neolithic, the other is the Bronze Age and Early Iron Age. The concentrations of flint flakes are interpreted as residuals of tool manufacturing. It seems most of them were manufactured elsewhere, though. Only one or two were made at the place where the flints were found. The stone-covered hillock with its different constructions is interpreted as a cult site with a possible ‘Harg’ at the top.